REVITALISASI ENTREPRENUERSHIP DI PONDOK PESANTREN - Halimatus Sakdiyah Halimatus Sakdiyah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2010)
Abstract: Pondok Pesantren (Islamic boarding school) as the Islamic education institution is the asset of Indonesian education. It can survive in the middle of modernity to defense its existency and characteristics, it needs to develop the talent and interest of santri (Pondok Pesantren student). This development must be organized in systematic and well-programmed plan. As the agent of development, pondok pesantren becames a brigde and media to solve social economic problems in society. The research finds solutions that the role of pondok pesantren as the agent of development now become an institution that can expand a business field. An economic business that independent, well established that revitalizes entrepreneurship. The objective is to overcome the problem of poverty and inadvertently as the impact by the subordination of Muslim in economis and business field. Santri is the pioner to create a business condition that can hold up the development of Indonesian economic Key Words: revitalisasi, entreprenuership, pondok pesantren dan agent of devolepment